The Role of Parathyroid Hormone Level as a Predictor of Hypocalcemia after Total Thyroidectomy for Thyroid Cancer: A Cross-Sectional Study - Danyal Khattak, Safia Bibi, Jawad Ahmed, Salman Ahmed Niaz Mangrio, Saddam Hussain, Muhammad Zafar, Irfan Ullah, Hanif Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypocalcemia is a common complication following total thyroidectomy, especially in patients undergoing surgery for thyroid cancer. Early identification of patients at risk for hypocalcemia is crucial for effective management. Objective: This study aimed to evaluate the role of parathyroid hormone (PTH) levels as a predictor of hypocalcemia following total thyroidectomy for thyroid cancer. Methods: This prospective observational study was conducted at institute of dental sciences Kohat during January 2022 to august 2022. A total of 195 patients were added in the study. Patients underwent a total thyroidectomy and were aged >18 years were included in the study. Patients with prior parathyroid disorders, those undergoing thyroidectomy for benign thyroid conditions, or those with a history of hypocalcemia or hypercalcemia were excluded. Results: The incidence of hypocalcemia within 24 hours post-surgery was 37%, with 28% at 6 hours, 36% at 12 hours, and 37% at 24 hours. The mean postoperative PTH level in the hypocalcemic group was significantly lower than in the non-hypocalcemic group at all time points. A PTH level below 15 pg/mL at 12 hours post-surgery had the highest sensitivity (83%) and specificity (75%) for predicting hypocalcemia. Surgical extent and preoperative low calcium levels were found to be significant factors associated with the risk of hypocalcemia. Calcium supplementation was required in 81% of hypocalcemic patients, with 19% needing intravenous supplementation. Conclusions: Postoperative PTH levels are a reliable predictor of hypocalcemia following total thyroidectomy for thyroid cancer. A PTH level below 15 pg/mL at 12 hours post-surgery is an effective cut-off for identifying patients at risk of hypocalcemia. Keywords: Parathyroid Hormone Level, Hypocalcemia, Total Thyroidectomy, Thyroid Cancer.